Environmental business strategy: the Portuguese case - Vinhas da Silva, R.; Teixeira, N. (Business Strategy and the Environment, 2006)
This study focuses on the adoption of environmental management systems and corporate social responsibility reporting as mechanisms for creating a differential advantage, looking at how different stakeholders in an organization perceive the importance of instituting these mechanisms as determinants of market success. The paper then aims to focus on environmental business strategy and corporate social responsibility reporting in companies, rather than prescribing policy for the entire sector. In so doing it postulates that compliance with market requirements on environmentally related issues, by instituting proper environmental management mechanisms and corporate social responsibility reporting, is a pre-requisite for acceptance of the firm and its products in the market. The paper is methodologically based on a set of 60 interviews conducted with various agents in the Portuguese textile industry, ranging from policy-makers to industrialists and NGOs, with a view to determining differences in perception between the various stakeholders.